THE STUDENTS’ INTEREST TOWARDS READING AL-QUR’AN - Ervika Dewi Wahyuni (Universitas Islam Balitar, 2018)
This research aims to explore, understand, and describe Universitas Islam Balitar students ’ interest towards reading Al-Qur ’an. Deploying qualitative method, observation, and interview, it appears that there were 65 out of 100 students who have finished reading Al-Qur ’an, and it was revealed that most of the students read Al-Qur ’an inside the college; nevertheless, most of them still read Al-Qur ’an haltingly. However, all the students said that they had great interest in reading Al-Qur ’an fluently either those who found themselves difficult to read Al-Qur ’an or even those who were unable to read Al-Qur ’an at all. The students were also aware that Al-Qur ’an must be read on a daily basis, and due to the importance of reading Al-Qura ’an nowadays, they thought that Reading Al-Qur ’an should be a particular subject in the university. The results revealed that a great number of students who have either finished reading Al-Qur ’an or read Al-Qu ’ran on a daily basis were found in Class A. The data were obtained from the students Attendance List under the supervision of Islamic Education lecturers in Primary Teacher Education study program at UNISBA Blitar